A closer look at invasiveness and relatedness: life histories, temperature, and establishment success of four congeners. Issue 11 (9th November 2020) - Rehage, J. S.; Maurer, E. F.; Lopez, L. K.; Sih, A.
Abstract: Successful invasive species are often closely related to other invasive species, suggesting that shared traits contribute to their invasion success. Alternatively, related species can differ in invasiveness, where some are highly invasive yet congeners seem unable to invade. Here, we compared the traits and establishment abilities of two highly successful invasive species, Gambusia affinis and G. holbrooki, to those of two close relatives, G. geiseri and G. hispaniolae . Using laboratory experiments, we compared low‐temperature tolerances and life histories of the four species. In a semi‐natural mesocosm experiment, we simulated the invasion of standardized, simple pond communities and examined the effects of these traits on each species' ability to become established. The invasive species, G. affinis and G. holbrooki, were more tolerant of low‐temperature stress, had greater fecundities, higher growth rates, and reached maturity sooner than G. geiseri and G. hispaniolae . In mesocosms, the invasive Gambusia exhibited higher intrinsic growth rates and carrying capacities and thus achieved and maintained larger populations than the two congeners. Only G. affinis and G. holbrooki successfully established long‐term populations in these experimental communities. G. geiseri and G. hispaniolae failed to establish as a result of 100% overwintering mortality. These results support the notion that the ability of invaders to cope with the abiotic conditions of target communities has a major effect on whether establishment occurs, while life histories play an important secondary role. Our results showed that invasiveness is likely not a trait of the entire genus Gambusia .